Satisfaction with Organization and Intention to Retain: The Mediating Role of Organizational Identity Complexity/Congruence of Outsourcing Labors - Turan, Aygul (KAMLA-RAJ ENTERPRISES, 2015)
Focusing primarily on organizational identity, the researcher argues theoretically and shows empirically that the mediating role of organizational identity complexity/congruence on the relationship between satisfaction with organization and intention to retain. In addition, they investigate for differences in organizational identity complexity, satisfaction with organization and intention to retain in terms of employees' demographic characteristics. Thus, the researcher focused on outsourcing labors having multiple organizational identities to delineate the employees' organizational identity,complexity/congruence and collected the data from outsourcing labors working in two public university campuses in Turkey. The results demonstrated that outsourcing labors experience congruence was not a complexity in organizational identity. Furthermore, it was recognized that organizational identity complexity/congruence mediates the relationship between satisfaction with organization and-intention to retain it. The researcher has also got scientific proof that there are significant differences in employees' satisfaction with an organization, organizational identity complexity/congruence and intention to retain in terms of employees' demographic characteristics.
Keywords: Intention to Retain; Organizational Identity Complexity; Satisfaction; MULTIPLE IDENTITIES; EMPLOYEE SATISFACTION; IDENTIFICATION; TURNOVER; COMMITMENT; MODEL; BOUNDARIES; LEVEL; WORK; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics